Literature Review: Factors Influencing the Interest of Indonesian Air Force (TNI AU) Applicants in Batam City - Uli, Mariati; Widodo, Sri (Dinasti International Journal of Management Science, 2025)
Previous research or relevant studies are crucial in scientific research or articles, as they serve to strengthen theories and explain the relationships or influences between variables. This article reviews the factors influencing the interest of applicants for the Indonesian Air Force (TNI AU) in Batam City. Optimizing applicant interest is highly expected by the organization to recruit high-quality human resources. Several factors influence the interest of applicants for the Indonesian Air Force. The purpose of this article is to identify these factors, and the findings indicate that; 1) Social media influences applicant interest; 2) The image of the Indonesian Air Force affects applicant interest;3) The recruitment process has an impact on applicant interest. This research is a literature study based on previous relevant studies, serving as a reference for future research in the field of human resource management to help organizations determine strategies and policies.